Vitamin D levels in women between 35 and 50 years old from the National University of Loja - Montoya Jaramillo, Veronica Luzmila (2023)
Vitamin D is a fat-soluble prohormone that is not only important for bone mineral metabolism, but also plays a crucial role in various physiological functions essential for general health, due to its specific receptor present in almost all cells. Among its beneficial effects are the improvement of the immune response, insulin secretion and the prevention of certain tumor processes. However, hypovitaminosis D is highly prevalent in Latin America and in Ecuador the presence of this problem has been confirmed in a large part of the population, especially in adult women. Objective: to evaluate the prevalence of hypovitaminosis D in women between 35 and 50 years old who work at the National University of Loja. In addition, the results obtained were related to age ranges and the possible relationship with the body mass index of the patients was evaluated. Methodology: quantitative, non-experimental and descriptive-correlational study. The sample was made up of 82 women. Results: 67.1% of the women presented hypovitaminosis D, of which 43.9% presented deficiency and 23.2% presented insufficiency. However, no statistically significant relationship was found between hypovitaminosis D and the age of the sample (p= 0.453), nor between hypovitaminosis D and body mass index (p= 0.204). Conclusion: although a high prevalence of hypovitaminosis D was found in this population, the levels are not related to age or body mass index.